2008
DOI: 10.1644/08-mamm-a-095.1
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Long-Term Capture Effects in Ursids: Implications for Wildlife Welfare and Research

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
192
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(200 citation statements)
references
References 70 publications
5
192
3
Order By: Relevance
“…Several studies have reported negative consequences of capture and marking on behavior (Pelletier et al, 2004), foraging efficiency (Saraux et al, 2011), rates of production and abandonment of young (Ballard and Tobey, 1981;Cô té et al, 1998), and survival (Oosthuizen et al, 2009). For example, Cattet et al (2008) found that repeated immobilization reduced mobility and body condition of grizzly bears (Ursus arctos horribilis) and black bears (Ursus americanus). Frequently, animals must be anesthetized more than once to change telemetry collars, download data, or measure growth.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported negative consequences of capture and marking on behavior (Pelletier et al, 2004), foraging efficiency (Saraux et al, 2011), rates of production and abandonment of young (Ballard and Tobey, 1981;Cô té et al, 1998), and survival (Oosthuizen et al, 2009). For example, Cattet et al (2008) found that repeated immobilization reduced mobility and body condition of grizzly bears (Ursus arctos horribilis) and black bears (Ursus americanus). Frequently, animals must be anesthetized more than once to change telemetry collars, download data, or measure growth.…”
Section: Introductionmentioning
confidence: 99%
“…For example, death of radio-marked individuals shortly following capture may be rare for species with high intrinsic rates of survival or where capture methods are less invasive. In such cases accounting for capture effects on mortality may be unnecessary, although nonlethal effects of capture may also persist in these situations (e.g., Cattet et al 2008). In situations where radio-marked individuals do die within the first few weeks following capture, a systematic approach to detecting shifts in mortality offers an empirically justified tool to identify thresholds for censorship.…”
Section: Discussionmentioning
confidence: 99%
“…However, Cattet et al (2008) indicated that capture and handling affected the daily movement rates of collared grizzly bears (U. arctos) and American black bears for relatively long periods of time (≥ 1 month). Future studies should examine whether capture and handling affects the movement patterns of collared bears, promoting nocturnal and/or nuisance activity instead of inherent crepuscular or diurnal activity (Reimchen 1998;Pelton 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Together with other investigations at nearby sites (Huygens and Hayashi 1999;Deguchi et al 2003), our approach using GPS technology may prove useful for developing management policies for nuisance black bears. However, our tracking period was brief, and bears must be collared in advance, especially if daily bear movement rates are evaluated more strictly (Cattet et al 2008). In future studies, simultaneous monitoring using GPS technology will be crucial for revealing social interactions among black bears.…”
Section: Discussionmentioning
confidence: 99%